Kajian Kebijakan Larangan Ekspor Bijih Nikel Indonesia - Fadlillah, Sarafina; Wahyuni, Krismanti Tri (Seminar Nasional Official Statistics, 2023)
Indonesia, as the world's largest producer of nickel ore, seeks to increase exports of processed nickel by establishing a policy of banning nickel ore exports. However, Indonesia is not among the fifteen largest nickel export countries in the world. This study aims to analyze general picture of Indonesia's processed nickel export volume, and analyze the effect of Indonesia's nickel ore export ban policy and other factors on Indonesia's processed nickel export volume. The methods used are line graphs and Error Correction Mechanism (ECM). In the long run, Indonesia's processed nickel export volume is influenced by the dummy of Peraturan Menteri ESDM Nomor 1 Tahun 2014, dummy of Peraturan Menteri ESDM Nomor 11 Tahun 2019, China's industrial GDP, real exchange rate of rupiah against US dollar, and world nickel processed prices. Meanwhile, in the short term, Indonesia's processed nickel export volume is influenced by the dummy of Peraturan Menteri ESDM Nomor 1 Tahun 2014, China's industrial GDP, and real exchange rate of rupiah against US dollar.